La Vulneración del Derecho a la Educación de los Niños, Niñas y Adolescentes portadores de VIH en los Centros Educativos” - Ramon Armijos, Rita Magaly (2016)
This research thesis entitled "The violation of the right to education of children and adolescents with HIV in schools" is the result of the study conducted of the current reality by coming through children HIV carriers and adolescents in schools, as they are discriminated against because they carry the virus, which affects them directly in their emotional, emotional, psychological, developmental and social state in which it is determined topics such as: The theoretical collection, which has focused relevant as the right to education, the principle of the best interests of the child, discrimination, violation of rights, HIV, AIDS, issues regarding the legal support in which is framed the law as is the Constitution of the Republic of Ecuador, Convention on the Rights of children, Organic Code of children and Adolescents, Organic Law of Intercultural education, Organic Code Integral Penal and terms concerning the doctrinal framework set topics such as: General Constitutional Principles, brief history of the evolution and development of the Right to Education, HIV in the world among others, more than the aforementioned add the study of specific cases, conducting surveys and interviews , allowed to obtain clear and precise criteria foundations, well known literature, which contributed to the verification of the objectives and benchmark test of the hypothesis proposed in this practice; to which was fundamental matter the study of both the Constitution and other laws that protect minors, and international instruments directly and immediately applicable in case of violation, discrimination, leading to a detailed study of compliance rights of children and adolescents belong to a group of priority.